Expression dynamics and physiologically relevant functional study of STEVOR in asexual stages of Plasmodium falciparum infection. (24th January 2017) - Singh, Himanshu; Madnani, Kripa; Lim, Ying Bena; Cao, Jianshu; Preiser, Peter R.; Lim, Chwee Teck
Abstract: The extensive modification of Plasmodium falciparum‐ infected erythrocytes by variant surface antigens plays a major role in immune evasion and malaria‐induced pathology. Here, using high‐resolution microscopy, we visualize the spatio‐temporal expression dynamics of STEVOR, an important variant surface antigens family, in a stage‐dependent manner. We demonstrate that it is exported to the cell surface where protein molecules cluster and preferentially localize in proximity to knobs. Quantitative evidence from our force measurements and microfluidic assays reveal that STEVOR can effectively mediate the formation of stable, robust rosettes under static and physiologically relevant flow conditions. Our results extend previously published studies in P. falciparum and emphasize the role of STEVOR in rosetting, an important contributor to disease pathology.